Main notions of axiological linguistics - Abdug‘affarova, Gulhayo Abdug‘affar qizi (The Lingua Spectrum, 2026)
This paper explores the fundamental issues of axiological linguistics, an interdisciplinary field concerned with how values are expressed and encoded in language. It examines the philosophical foundations of axiology and traces its development across various disciplines, highlighting its significance for understanding the role of values in shaping human behavior, social norms, and cultural patterns. Particular emphasis is placed on evaluation as the central category of axiological analysis, including its internal structure, main types, and linguistic means of expression at different levels of language. The study reviews classifications proposed by leading scholars and analyzes both objective and subjective evaluations, as well as their inherently social character. In addition, the paper discusses the concept of social values and their influence on collective consciousness, interpersonal interaction, and communicative practices. Overall, the research demonstrates that language functions not only as a tool for communication but also as a powerful mechanism for constructing, preserving, and transmitting value systems within society.